UiTM signs Memorandum of Understanding (MoU) with Dandy Modern Food Sdn. Bhd. - Othman, Nor Azlan; Bakhari, Nor Aziyah (UiTM News Hub, 2021)
A Memorandum of Understanding (MoU) has been signed between Universiti Teknologi MARA (UiTM) and Dandy Modern Food Sdn. Bhd. at the Dandy’s restaurant. Dandy Modern Food Sdn. Bhd. was represented by YBrs. Mr Jamal Haddad, Managing Director and witnessed by YBrs Mdm. Michelle Yeo Suk Ling, Executive Director. Meanwhile, UiTM Cawangan Pulau Pinang (UiTMCPP) was represented by YBhg. Prof Ts Dr Salmiah Kasolang, Rector UiTMCPP and witnessed by YBrs. Associate Prof ChM Dr Nor Aziyah Bakhari, Deputy Rector of Research & Industrial Linkages. This MoU is initiated by lecturers from the Faculty of Hotel & Tourism Management (FPHP) UiTMCPP; Chef Ahmad Fauzan, Chef Mohd Syafiq, Chef Putri Dahlia, Chef Nik Mohd Shahril, Associate Prof Dr. Norfezah and Dr. Suria.